Efektivitas Fintech Melalui Digital Payment terhadap Perkembangan UMKM di Indonesia - Windi Mayani Dalimunthe; Tri Inda Fadhila Rahma; Wahyu Syarvina (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to see the effectiveness of fintech through digital payments on the development of in Indonesia with limited problems in the city of Medan. The type of research used is descriptive combination. The data source used is primary data by distributing questionnaires to respondents in this case business actors, micro, small and medium enterprises which are supported by research through interviews with business actors, micro, small and medium enterprises to see opinions about the application of digital payments on his business. The analytical technique used in this study is simple linear regression analysis by testing using the SPSS 26 application. The results of the study state that the digital payment variable has a positive and significant effect on the development of micro, small and medium enterprises. Meanwhile, based on the results of the interviews, it was taken that there was a positive impact from the provision of digital payments for in providing security, convenience and also speed in carrying out transaction processes Keywords: Fintech, Digital Payment, Bussines, Micro, Small and Medium